2018
DOI: 10.1016/j.neuroimage.2018.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high resolution blood volume fMRI and BOLD fMRI in humans at 9.4 T: Capabilities and challenges

Abstract: Functional mapping of cerebral blood volume (CBV) changes has the potential to reveal brain activity with high localization specificity at the level of cortical layers and columns. Non-invasive CBV imaging using Vascular Space Occupancy (VASO) at ultra-high magnetic field strengths promises high spatial specificity but poses unique challenges in human applications. As such, 9.4 T B1+ and B0 inhomogeneities limit efficient blood tagging, the specific absorption rate (SAR) constraints limit the application of VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 63 publications
6
58
0
Order By: Relevance
“…The somatosensory CBV changes in response to whisker stimulation peak in the range of 5%-10% (compared to the baseline CBV). Such amplitudes are consistent with previously reported ΔCBV estimates in the pre-clinical domain (Hillman et al 2007;Kennerley et al 2005;2012a;Lee et al 2001;Tian et al 2010), whereas they are about 5-10 times smaller than previously reported VASO signal changes in humans (Beckett et al 2020;Chai et al 2019;Finn et al 2019;Guidi et al 2017;Huber et al 2018;Kurban et al 2020;Persichetti et al 2020;Yang and Yu 2019;Yu et al 2019).…”
Section: Concomitant Ois and Vasosupporting
confidence: 93%
See 1 more Smart Citation
“…The somatosensory CBV changes in response to whisker stimulation peak in the range of 5%-10% (compared to the baseline CBV). Such amplitudes are consistent with previously reported ΔCBV estimates in the pre-clinical domain (Hillman et al 2007;Kennerley et al 2005;2012a;Lee et al 2001;Tian et al 2010), whereas they are about 5-10 times smaller than previously reported VASO signal changes in humans (Beckett et al 2020;Chai et al 2019;Finn et al 2019;Guidi et al 2017;Huber et al 2018;Kurban et al 2020;Persichetti et al 2020;Yang and Yu 2019;Yu et al 2019).…”
Section: Concomitant Ois and Vasosupporting
confidence: 93%
“…Slice selective slab-inversion (SS-SI) VASO is widely used across the literature for non-invasive imaging of microvascular layer-specific signal responses (Beckett et al 2020;Chai et al 2019;Finn et al 2019;Guidi et al 2017;Huber et al 2018;Kurban et al 2020;Persichetti et al 2020;Yang and Yu 2019;Yu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the inflow effects commonly seen in BOLD images, all VASO sequences are at risk of artifacts due to the inflowing of uninverted blood to the imaging volume, e.g. in areas of very short arrival time such as large arteries (70), potentially reducing any observed VASO signal change. The use of shorter TIs with adjusted inversion efficiency, as performed here, can help avoid these artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…arterial spin labeling) 20 or CBV fMRI (e.g. vascular space occupancy or VASO) [21][22][23] to detect brain dysfunction as well as monitor disease progression.…”
Section: Introductionmentioning
confidence: 99%